SNi from SN2: a front-face mechanism ‘synthase’ engineered from a retaining hydrolase - Iglesias-Fernández, Javier; Hancock, Susan M.; Lee, Seung Seo; Khan, Moala; Kirkpatrick, Jo; Oldham, Neil J.; McAuley, Katherine; Fordham-Skelton, Anthony; Rovira, Carme; Davis, Benjamin G. (Nature Publishing Group, 2017)
SNi or SNi-like mechanisms, in which leaving group departure and nucleophile approach occur on the same ‘front’ face, have been observed previously experimentally and computationally in both the chemical and enzymatic (glycosyltransferase) substitution reactions of α-glycosyl electrophiles. Given the availability of often energetically comparable competing pathways for substitution (SNi vs SN1 vs SN2) the precise modulation of this archetypal reaction type should be feasible. Here, we show that the drastic engineering of a protein that catalyzes substitution, a retaining β-glycosidase (from Sulfolobus solfataricus SSβG), apparently changes the mode of reaction from “SN2” to “SNi”. Destruction of the nucleophilic Glu387 of SSβG-WT through Glu387Tyr mutation (E387Y) created a catalyst (SSβG-E387Y) with lowered but clear transglycosylation substitution activity with activated substrates, altered substrate and reaction preferences and hence useful synthetic (‘synthase’) utility by virtue of its low hydrolytic activity with unactivated substrates. Strikingly, the catalyst still displayed retaining β stereoselectivity, despite lacking a suitable nucleophile; pH-activity profile, mechanism-based inactivators and mutational analyses suggest that SSβG-E387Y operates without either the use of nucleophile or general acid/base residues, consistent with a SNi or SNi-like mechanism. An x-ray structure of SSβG-E387Y and subsequent metadynamics simulation suggest recruitment of substrates aided by a π-sugar interaction with the introduced Tyr387 and reveal a QM/MM free energy landscape for the substitution reaction catalyzed by this unnatural enzyme similar to those of known natural, SNi-like glycosyltransferase (GT) enzymes. Proton flight from the putative hydroxyl nucleophile to the developing p-nitrophenoxide leaving group of the substituted molecule in the reactant complex creates a hydrogen bond that appears to crucially facilitate the mechanism, mimicking the natural mechanism of SNi-GTs. An oxocarbenium ion-pair minimum along the reaction pathway suggests a step-wise SNi-like DN*ANss rather than a concerted SNi DNAN mechanism. This first observation of a front face mechanism in a β-retaining glycosyl transfer enzyme highlights, not only that unusual SNi reaction pathways may be accessed through direct engineering of catalysts with suitable environments, but also suggests that ‘β-SNi’ reactions are also feasible for glycosyl transfer enzymes and the more widespread existence of SNi or SNi-like mechanism in nature.